PENGARUH KINERJA DINAS KESEHATAN KOTA PEKANBARU TERHADAP PERBAIKAN GIZI MASYARAKAT DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU TAHUN 2012-2015 - Fiandy, Sandy Reintar; ", Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is motivated by the lack of employee performance to the improvement of community nutrition. The problems that arise from this research is how much influence the performance of employees to the improvement of community nutrition. The purpose of this study is to determine the effect of employee performance on community nutrition improvement in Tenayan Raya District.The type of this research is quantitative descriptive research, the sample is determined by researchers as many as 51 employees, data collection techniques used by the author through literature study, observation and questionnaires. Sources of data in this study is using primary data and secondary data. In processing the data the author uses SPSS 17.0 program by using simple linear regression formula with the formula Ã = a + bX.Based on the results of the study found that the performance of employees affect the improvement of community nutrition with a correlation value of 0.916. The value of 0.916 shows the correlation between independent variables (employee performance) and the dependent variable (community nutritional improvement) is in a very strong correlation category (0.800 - 1,000). This is reinforced by hypothesis test result with t-count value of 23.123 When compared with the t-table value of 0.276 then the t-count obtained is much greater than the value of t-table or t arithmetic> t table (23.123> 0.276), meaning Ho is rejected and Ha accepted. Thus it can be concluded that the variable inerja Employees significantly influence the Community Nutrition Improvement. From the results of coefficient determiniasi test can be seen that the value of coefficient of determination or R Square of 0.916 or 91.6%. This shows that the variables studied (employee performance) have an impact on the improvement of community nutrition by 91.6%.Keywords: Influence, Performance, Employee